Diet, Microbiota, and Colorectal Cancer - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2014)
Colorectal cancer (CRC) is the third most common cancer in the world causing nearly 500,000 deaths every year. In addition to genetic background, environmental factors including diet and lifestyle are accepted as major contributors to adenoma and CRC development. Lifestyle factors include high BMI, obesity, and reduced physical activity. Growing interest and accumulating data on human microbiota implicate that host-microbe interplay has an important role in the development of metabolic, neoplastic, and inflammatory diseases. Findings from recent studies suggest that colon cancer risk is determined by the interaction between diet and gut microbiota. Dietary changes affect gut microbiota and conversely microbiota mediates the generation of dietary factors triggering colon cancer. Identification of the microbial communities associated with carcinogenesis is of crucial importance. Nowadays, with the evolvement of culture-independent molecular techniques, it has become possible to identify main bacterial species in healthy individuals, inflammatory conditions, and CRC. Some recent studies have shown the differences in intestinal microbiota between colon cancer patients and healthy individuals. Animal studies have provided a better understanding of interaction between pathobionts and symbionts in the development of colon cancer. There is no single causative organism identified in CRC; however, there is strong evidence that reduction of protective bacteria, increase in some bacteria (ie, fusobacterium members; Bacteroides/Prevotella), and age-related changes in microbiota have an impact on adenoma or cancer development. Future studies will enable us to understand procarcinogenic and anticarcinogenic mechanisms and give insights to rational manipulation of the microbiota with prebiotics, probiotics, or dietary modifications.
Keywords: colorectal cancer; microbiota; diet; dysbiosis; probiotics; GUT MICROBIOTA; INTESTINAL MICROBIOTA; MEDITERRANEAN DIET; PREVENTION; METABOLITES; MICROFLORA; PROBIOTICS; CULTURE; DISEASE; HEALTH